Apexification treatment of immature permanent maxillary first molar with taurodontism: a case report - Ferianto, Ferianto; Gartika, Meirina (Padjadjaran Journal of Dentistry, 2025)
Introduction: Taurodontism is a rare developmental abnormality affecting the permanent molars, resulting from the incomplete invagination of Hertwig’s epithelial root sheath at the proper horizontal level. Apexification treatment of a taurodont tooth is challenging and requires special attention due to the difficulty in finding the orifices, as well as the complexity involved in the preparation and obturation of the root canals. Case Reports: This case report aims to present the clinical management of apexification in an immature permanent molar with taurodontism, highlighting, endodontic treatment strategy, and the rationale for using calcium hydroxide as the material of choice. The apexification treatment with calcium hydroxide was performed on the immature maxillary left first molar (tooth 26) of an 11-year-old girl patient diagnosed with symptomatic irreversible pulpitis and mesotaurodontism. After six months, no subjective or clinical symptoms were reported. Although apical closure was not clearly evident on radiography, an apical stop was observed during clinical examination. Following this evaluation, tooth 26 was obturated with gutta-percha combined with a bioceramic sealer, and subsequently restored using direct composite restoration. An evaluation was performed three months post-treatment, incorporating clinical examination and radiographic and cone-beam computed tomography (CBCT) imaging. Conclusion: This case report highlights the successful apexification of a maxillary first molar with taurodontism using calcium hydroxide. The patient remained asymptomatic throughout treatment, with radiographic evaluations indicating conditions within normal limits. Cone-beam computed tomography (CBCT) confirmed adequate obturation extending to the apical region and demonstrated definitive apical closure after six months follow-up.